THE EFFECT OF ARBUSCULAR MICHORRIZA FUNGI AND ORGANIC FERTILIZER ON THE GROWTH OF SUNFLOWER (HELIANTHUS ANNUUS L.) ON CRITICAL LAND OF FORMER IRON ORE MINE IN LHOONG - ACEH BESAR - Suwarniati Suwarniati; Ulia Hanum; muslim muslim (Jurnal Natural, 2018)
The study determines the effect of arbuscular mycorrhiza fungi (AMF) and organic fertilizer on sunflower growth (Helianthus annuus L.) in former iron ore mine in Lhoong, Aceh Besar. The Randomized block design is 2×3 factorial with 4 replications was used. The first factor: Without Mycorrhiza and Mixed Mycorrhiza. The second factors were Without Fertilizer, Manure, and Guano. The results showed that at α = 5% variation analysis, AMF had very significant effect on plant height in 10 d After Planting (DAP), leaf number 50 DAP, fresh  weight of top-trimmed, and AMF colonized roots. Furthermore, it showed a significant effect on plant height 40 and 50 DAP, leaf number 20, 40 DAP and dry weight of top-trimmed. Fertilizer were significantly affected on plant height in 10 and 20 DAP, leaf number 50 DAP and fresh/dry weight of the top-trimmed. It showed a significant effect on plant height 30 DAP and leaf number 40 DAP. Mixed Mycorrhiza and Guano showed the best results. The interaction between AMF and fertilizer had a significant effect on plant height at 50 DAP and fresh  weight of the top-trimmed. Mixed Mycorrhiza and Manure showed the best results on 50 DAP with increasing in plant height, while Mixed mycorrhiza and Guano increased fresh weight of the top-trimmed.Keywords: arbuscular mycorrhiza fungi (AMF), Helianthus annuus L., critical land, organic fertilizer, sunflower growth.